Affinity for glycoproteins of bacteria found in the respiratory tract in cystic fibrosis - Saggers, B. A. (1970)
The attraction of bacteria commonly found in the respiratory tract in cystic fibrosis to glycoprotein at pH 7 has been studied. The effect of washing on the removal of bacteria from the glycoprotein has also been investigated, and the value of doing both washed and unwashed sputum cultures is discussed.